1D N-type SnO2 nanofibers coexisted with P-type Co3O4 cubes for highly selective acetone sensor. (February 2019) - Tang, W; Li, D W; Du, X J; Yu, J; Sun, Q Q
Abstract: 1D n-type SnO2 nanofibers coexisted with p-type Co3 O4 particles were synthesized by electrospinning with subsequent hydro-thermal process. The morphology and composition of Co3 O4 /SnO2 were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM). XRD patterns showed that the synthesized Co3 O4 /SnO2 were assigned to cubic Co3 O4 and tetragonal rutile structure of SnO2 without any other impurity peaks. A possible growth mechanism was proposed to describe the formation of hierarchical SnO2 nanofibers coexisted with Co3 O4 cubes. The Co3 O4 /SnO2 compound exhibited a relatively highly selective response to acetone and stable acetone sensing performance after a long period of aging. The Co3 O4 /SnO2 compound had a p-type response. It may be ascribed to the high coverage of p-type Co3 O4 on n-type SnO2 . The excellent acetone sensing properties of Co3 O4 /SnO2 nanostructures may be attributed to p-n junctions between Co3 O4 and SnO2 nanograins as well as the unique coexistence structure of nanofibers and cubes.